Tembok Benteng Kotagede (Baluwarti) Yogyakarta Berangsur-Angsur Musnah! - Sugeng Riyanto (Berkala Arkeologi, 2006)
As a cultural heritage, Kotagede in Yogyakarta, which was built in the sixteenth century, is within the framework of conflict. It is a fact that baluwarti as the physical boundary of the city and the most important part of its time is gradually disappearing. On the other hand, the development of the archaeological discipline has actually placed this kind of issue as part of its study. In this case, the political and public context are also positioned as stakeholders of cultural heritage, and not merely oriented to the academic context. Perhaps a theoretical, philosophical, and historic framework is needed to see how the walls of the Kotagede fortress are gradually being destroyed.